Impact of Electric Vehicle Charging Behavior on the Transmission System and the Electricity Market in Germany - Teske, Franz; Funk, Felix; Fehrle, Adrian; Franke, Jörg (2022 12th International Electric Drives Production Conference, EDPC 2022 - Proceedings, 2022)
The increasing market penetration of electric vehicles (EVs) not only creates challenges at the lower voltage levels of the power grid but also significantly impacts the national energy system. The latter effect is, however, rarely discussed in current research, which primarily focuses on the integration of EVs into the distribution grid. This paper, therefore, examines the impact of defined EV penetration levels and user behaviors on the national transmission grid and wholesale electricity prices. For this purpose, a fundamental model of the German power system, consisting of the loads, the power plants, and the transmission grid, is created. This model is then used to simulate and analyze the impact of selected charging behaviors. It is shown that wholesale electricity prices and transmission grid utilization hardly depend on the chosen hourly charging profile of EVs. Rather, the maximum power and the amount of electricity are the most significant influences. Additional load leads to a small increase in the electricity price, but not to an aggravation of line congestion problems.
CRIS-Team Scopus Importer:2023-03-07
Keywords: charging stations; grid impact; power generation economics; power grids; power markets; transmission grid